An Investigation on Kumis Treatment in the Context of Health Tourism - Erdem, Barış (Turizam, 2018)
Continuing growth and expansion of international tourism around the world has increased competition between countries, which desire to expand shares in the industry. Therefore, many countries are trying to use efficiently their touristic potential, while displaying their efforts. The result of increasing tourism demand is formation of new destinations, which emerge in new market areas. One of these new markets is health tourism. Nowadays health tourism is attracting more attention as a rapidly growing alternative market. As a fact, health tourism is a market worth approximately 100 billion dollars today. Medical tourism travel become especially popular tourism activity and revenue from medical tourism made this field more attractive. Tourists traveling for medical purpose spend their time on recreation, sport and other activities during these tours, however, the main purpose of medical tourism not only getting treatment but also travelling. Kumis, which is composed from fermented mare milk, has been used in central Asian for medical purposes for centuries and this type of treatment is known to have many benefits. This descriptive study focuses on medical treatment within health tourism. In this context; the definition, content, historical development and benefits of kumis treatment are emphasized. Besides, information has been given about countries which use kumis treatment in the world. The findings of the study are expected to bring a new perspective to the health tourism literature.